Komunikasi dalam Platform Online Crowdfunding: Tinjauan Literatur Sistematis: Communication in Online Crowdfunding Platforms: A Systematic Literature Review ​ - Wismashanti, Rizky Amalia; Irwansyah (Pandawan Incorporation, Alphabet Incubator Universitas Raharja, 2024)
This article was prepared to determine the role of communication in crowdfunding on online platforms in the last three years. In answering this research problem, a research based on a systematic literature review was carried out. The research was conducted using Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA). The results of the research found that communication contributed significantly to crowdfunding in the last three years. This research has several findings. First, the use of social media or media networks will be more effective when communicators are able to provide information about campaign development. Narrative and message persuasion are important to pay attention to for the success of crowdfunding. Second, trust is critical for success in the online marketplace, especially in crowdfunding. Thus, social media engagement and information sharing on social media are very important for the success of crowdfunding. This is also supported by good comments from consumers on social media. Third, companies that carry out crowdfunding campaigns on a basis other than donations must be able to provide reciprocity that attracts people to take part in the crowdfunding carried out. In these three findings, effective communication has a significant contribution to the success of crowdfunding. The conclusion of this research, looking at the contribution of communication in crowdfunding, further research and direction is needed regarding communication in crowdfunding.